The Effect of Using the “Grammar Tool: Pronoun” on Understanding Possessive Pronouns and Possessive Adjectives - Ridha Sakinah Alkadri; Yuli Tiarina (Universitas Negeri Padang, 2022)
This study aims to determine whether or not using the Grammar Tool: Pronoun application has a significant impact on students' understanding of possessive pronouns and possessive adjectives. Participants in this study are seventh-grade students at SMPN 52 in Jakarta. There are 216 students that classified into six classes. VII A is selected as the experimental class by the researcher utilizing a cluster random sampling method to select one class. This research was held over eight meetings and this research was carried out outside of school hours. The researcher used the multiple choice test as the instrument to collect the data. There were 40 questions but after the validity and reliability test, only 29 questions that can be used as the instrument for this research. After the research is done, it is possible to say that using the Grammar Tool: Pronoun has an effect on how well students understand possessive pronouns and possessive adjectives there was an improvement of the students understanding on possessive pronouns and possessive adjectives. It can be proved by the data findings and discussion. The results of the data analysis indicated that the null hypothesis examined in the study cannot be accepted because the significant value of the 2-tailed test was less than 0.05 (0.05). The alternative hypothesis, which indicated that the use of the Grammar Tool: Pronoun is effective on students' understanding of possessive pronouns and possessive adjectives, was accepted as a result of this study.